Takotsubo cardiomyopathy in amiodarone-induced hyperthyroidism. (15th February 2017) - Capel, Ismael; Tasa-Vinyals, Elisabet; Cano-Palomares, Albert; Bergés-Raso, Irene; Albert, Lara; Rigla, Mercedes; Caixàs, Assumpta
Summary: Takotsubo cardiomyopathy (TC) is an atypical, severe but reversible form of acute heart insufficiency. It typically presents with left ventricular failure, transient apical and mid-segments hypokinesis, absence of significant coronary stenosis and new electrographic abnormalities and/or elevation in serum cardiac enzymes. Although TC ('broken heart syndrome') has classically been associated with emotional trauma, evidence suggests that other precipitants might exist, including iatrogenic and thyroid-mediated forms. Thyroid disease is a relatively common comorbidity in TC patients. We report a case of TC in a postmenopausal female with no history of emotional trauma or other potential precipitant factors who was diagnosed with amiodarone-induced hyperthyroidism during her hospital stay. Though some case reports of thyroid-related TC exist, we are not aware of any other reported case of TC precipitated by amiodarone-induced hyperthyroidism. Learning points: TC is a relatively new, rare, transient, severe, but reversible cardiovascular condition that is characterized by an acute left ventricular cardiac failure, which can clinically, analytically and electrocardiographically mimic an acute myocardial infarction. Many precipitant factors have been described in TC, being the most classical and emotional trauma. However, thyroid dysfunction is also a significant condition frequently found in patients with TC. A hypercatecholaminergic state leading to cardiomyocyte damage has been established as the main fact of TC physiopathology. Hyperthyroidism induces an upregulation of β-adrenergic receptors. Both hyperthyroidism and hypothyroidism have been related with TC development. Most reported cases of TC involving thyroid dysfunction correspond to hyperthyroidism due to Graves–Basedow disease, but there are also descriptions with severe hypothyroidism, radioiodine treatment or thyroid surgery. Amiodarone is a class III antiarrhythmic agent widely used, and it is a well-known cause of thyroid dysfunction, which can present either with hypothyroidism or hyperthyroidism, as approximately 40 percent of the amiodarone molecule is composed of iodine. In this case, a type II amiodarone-induced hyperthyroidism was the precipitant factor of a TC in a patient with a pre-existing atrial fibrillation. Given the high prevalence of atrial fibrillation and the wide use of amiodarone, the risk of this iatrogenic effect should be taken into account.